Some results on analogous continued fraction of Ramanujan - Srivastava, Bhaskar (Italian Journal of Pure and Applied Mathematics, 2011)
We give a differential for \(\frac{1}{C(q)}\) and prove an identity which is analogous to Ramanujan's Entry 3.2.7. We also give a simpler proof for Entry 9(v).